IMPROVING CHILDREN'S CREATIVITY THROUGH ENVIRONMENTAL EXPLORATION ACTIVITIES - Mamma, Agustinus Tandilo; Sirjon, Sirjon (Journal of Early Childhood Education (JECE), 2021)
This study aimed to increase children's creativity by exploring the natural surroundings of group A children at TK Tunas Dansari Dosay, Jayapura Regency. The subjects of this study were 15 children. This research is a classroom action research method using the action model from Kemmis and Mc Taggart. Data collecting was observation and documentation—data analysis using qualitative descriptive analysis. The results showed an increase in the creativity of group A children in TK Tunas Dansari Dosay. The research data showed that before the action, the average group value was 45.55%. After being given action cycle I, the average result was 55.55%; action II amounted to 63.33% and increased in action III 67.22%. In cycle II, an action I increased to 71.67%, action II increased to 75.55%, and action III increased to 81.10%. Based on these data, exploring the surrounding nature can increase the creativity of group A children at TK Tunas Dansari Dosay, Jayapura Regency.